2020
DOI: 10.3390/ceramics3010015
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Mechanism of A Density-Reduced Steel Ladle Lining Containing Porous Spinel-Calcium Aluminate Aggregates

Abstract: Refractory monolithics for steel ladle linings are typically products with low porosities and high bulk densities. They achieve high temperature, penetration, and corrosion resistance. Despite the high density of these products, which is due to the low porosity of the aggregates, their matrices still exhibit a high amount of pores. Since calcium magnesium aluminate (CMA) has already proven its resistance to penetration and corrosion as a binder in the matrix, this paper investigated if alumina spinel refractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Hence, the penetration index was one of the important factors to evaluate the slag resistance of castables. It was indicated that the complex phase composition of CMA aggregates was beneficial to form calcium aluminum silicate glass phase, which can prevent slag from deep penetration in refractories [ 14 , 15 , 16 ]. This mechanism was mainly concerned the chemical composition of CMA aggregates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the penetration index was one of the important factors to evaluate the slag resistance of castables. It was indicated that the complex phase composition of CMA aggregates was beneficial to form calcium aluminum silicate glass phase, which can prevent slag from deep penetration in refractories [ 14 , 15 , 16 ]. This mechanism was mainly concerned the chemical composition of CMA aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…The slag resistance of magnesia-carbon (MgO-C) bricks for steel ladle linings was significantly improved with CMA aggregates addition as a consequence of an in situ formation of a protective layer on the surface of bricks [ 14 , 15 ]. The corrosion mechanism of alumina-spinel castables with CMA aggregates addition has been demonstrated by Wöhrmeyer et al The results indicated that a thin densified zone formed and blocked the slag penetration into the porous matrix and the porous aggregates [ 16 ]. However, the comprehensive performance of castables was critical for the applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, novel calcium magnesium aluminate (CMA) materials containing spinel and calcium aluminate have been developed (MagArmour, Imerys, France). Wöhrmeyer et al reported that the incorporation of CMA in alumina-spinel castables could effectively inhibit the penetration of slag into the matrix and improve the energy efficiency of steel ladles [ 18 ]. Tang et al investigated the influence of CMA aggregates on the properties of alumina-spinel refractory castables.…”
Section: Introductionmentioning
confidence: 99%
“…Later, a series of lightweight porous aggregates (alumina, mullite, spinel, and cordierite) was prepared via an in-situ pore-forming technique by Li et al [14] and Yan et al [15][16][17][18][19]. In addition, lightweight porous aggregates of calcium aluminates and spinel have been reported [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to common dense refractory materials, the lightweight refractories fabricated with such lightweight aggregates exhibited lower bulk density and thermal conductivity [19,21].…”
Section: Introductionmentioning
confidence: 99%